If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 19 + -15 + -18z = -16 + -19z Combine like terms: 19 + -15 = 4 4 + -18z = -16 + -19z Solving 4 + -18z = -16 + -19z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '19z' to each side of the equation. 4 + -18z + 19z = -16 + -19z + 19z Combine like terms: -18z + 19z = 1z 4 + 1z = -16 + -19z + 19z Combine like terms: -19z + 19z = 0 4 + 1z = -16 + 0 4 + 1z = -16 Add '-4' to each side of the equation. 4 + -4 + 1z = -16 + -4 Combine like terms: 4 + -4 = 0 0 + 1z = -16 + -4 1z = -16 + -4 Combine like terms: -16 + -4 = -20 1z = -20 Divide each side by '1'. z = -20 Simplifying z = -20
| -3.62-15.1d=16.78-14.4d+2.3d | | t-67=-2t-7 | | 14z=266 | | 9x^2+15=15 | | 6x=360(24) | | 3(-2x+4)=6(x-2) | | m-1/23/2 | | -20-20u=-13u+19+3 | | C=3.14(14) | | 12x^5y^8/4x^2v^3 | | -5a+6=a+150 | | 2x=35(7) | | (6x-4)+(6x-4)+(2x+10)+(2x+10)=(6x-4)+(6x-4)+(2x+10)+(2x+10) | | y=x+35 | | 18-17m=-13m-6 | | 3(-2x+4)=6(x+2) | | 5w-16=24 | | -y=-3y-14 | | 6x-8x+2=-3 | | -4r+11=-7r-1+3r | | 10p+8p=p+44 | | 15-3y=4x | | 6x=20(8) | | -6q-5=2q+3-10q | | r+192=-8r+3 | | 5x^2+20=5 | | 5(3x+9y)= | | 6x-8x+2=3 | | 4xy/4x=8x^2/4x | | (2x-2)+(5x-13)=90 | | 92=4u+12 | | 2p=36 |